Metal‐Organic‐Framework‐Derived Bismuth Nanosheets for Electrochemical and Solar‐Driven Electrochemical CO2 Reduction to Formate. Issue 5 (1st February 2021) - Zhang, Bo; Cao, Shuyan; Wu, Yunzhen; Zhai, Panlong; Li, Zhuwei; Zhang, Yanting; Fan, Zhaozhong; Wang, Chen; Zhang, Xiaomeng; Hou, Jungang; Sun, Licheng
Abstract: Electrochemical CO2 reduction is a promising way to achieve CO2 fixation and energy storage. However, it is a challenge to develop the potential electrocatalysts with excellent performance and selectivity. Herein, bismuth nanosheet arrays (Bi/CC‐17) are prepared through an in situ electrochemical transformation strategy by use of Bi‐based metal organic frameworks (MOFs) as the precursors, which are then attached on carbon cloth. The as‐synthesized Bi/CC‐17 nanosheet arrays achieve considerable partial current density of 45 mA cm −2 and remarkably high faradic efficiency of 98 % at the potential of −1.1 V versus RHE for the conversion of CO2 to formate, outperforming most previously reported electrocatalysts. In particular, the solar‐driven In2 O3 /In2 S3 ∥Bi two‐electrode system with a In2 O3 /In2 S3 ‐based photoanode and typical Bi‐based cathode achieves high faradaic efficiencies of ≥90 % for HCOOH formation, from −0.6 to −1.6 V versus the counter electrode (vs. CE). This work paves an avenue to develop MOF‐derived electrocatalysts for sustainable conversion of CO2 into valuable chemicals. Abstract : Metal organic framework (MOF)‐derived Bi/CC‐17 nanosheet arrays are successfully fabricated by using a simple electroreduction method. The as‐synthesized Bi/CC‐17 nanosheet arrays achieve an extremely high partial current density of 45 mA cm −2 and remarkably high faradic efficiency of 98 % at the potential of −1.1 V vs. RHE for the conversion of CO2 to formate, outperforming most reported electrocatalysts. This work paves an avenue to develop MOF‐derived electrocatalysts for the sustainable conversion of CO2 into valuable chemicals.